Effects of algae and hydrophytes on the inorganic phosphorus pool of shallow hypereutrophic Lake Taihu. Issue 1 (25th August 2021) - Li, Xiaojun; Xu, Xiaoguang; Zhao, Yanping; Han, Ruiming; Wang, Guoxiang
Abstract: Sedimentary phosphorus is a crucial potential source of phosphorus in the eutrophic lake ecosystem. Different ecological types are supposed to affect the presence and variation of sediment phosphorus. On the basis of field investigations, the total sediment phosphorus load in Zhushan Bay was 1, 457.48 mg/kg, nearly four times that of the hydrophyte-dominated area. Thereinto, 41.1% was in the form of iron and aluminum-bound phosphorus, which explicitly indicated the phosphorus contamination there. Analytical methods such as Pearson correlation, contamination assessment and principal component analysis were conducted to find out that 'contamination' was not equivalent to 'release risk'. The contamination classification of East Lake Taihu was 'clean' in general. However, 63.3% of the total phosphorus could be mobilized under certain conditions. Therefore, light phosphorus loading does not equate to less release risk. In the long run, the implicit phosphorus release by the activation of organic phosphorus in hydrophytic areas needs close attention. This study provides a reference to understand the influence of hydrophytes and algae on the phosphorus cycle of sediment. HIGHLIGHTS: Light phosphorus loading does not equate to less release risk. Under anaerobic conditions, more than 50% of organic phosphorus could be activated. In the long run, the phosphorus release potential of the hydrophytic bay needs close attention. The negative effects of algae on sediment phosphorus mainly start since their decay. Graphical Abstract